O código de ética como ferramenta da gestão organizacional: uma análise sobre a gestão da ética no poder judiciário - Silva, Miguel Bruno Soares (2018)
The ethical question has become a central issue, in a remarkable scenario of afflictions and so many uncertainties about the future of the country, in which arises from the heart of the brazilian society a timely critical reflection on the values that guide it, as well as on the structures from which are expected to production of rights, protection of social interests and an ethical model to be reproduced by citizens. This research sought, through literature review and survey, to know the effectiveness of the implementation of the Code of Ethics of Servers of the Court of Justice of the State of Sergipe as a tool on the management and standardization of the ethical conduct of the servants, based on the investigation of the levels of their familiarity and exposure to issues related to ethics in the institution. The results allow to state, among other conclusions, that, although the servers consider themselves responsible for their ethical conduct within the organization, both the disclosure and the implementation of the Code among the servers must be improved so that its content can provide criteria and guidelines so that people find ethical ways of conducting themselves within the organization or even outside it. Therefore, the establishment of an Ethics Committee is an essential step that must be taken in respect of the fundamentally citizen character that the management of ethics presupposes, so that the instrument becomes more than a mere instrumental formality and effectively get to represent an institutional commitment, based on the values and principles of the organization.